Al-Qur'an sebagai Permata Sastra - Hasanuddin Chaer; Abdul Rasyad; Ahmad Sirulhaq; Djamil Abdurachman Malik (PALAPA, 2022)
The text of the Qur'an is a great expression that contains experiences, thoughts, feelings, ideas, enthusiasm, beliefs, and also noble teachings as objects of critical study through literary paradigms to find sources of literary inspiration, beautiful and comprehensive in various styles of language. This study uses Barthes' literary theory through three aspects of literary meaning; connotation, denotation, and myth. With details of intertextuality analysis in examining several objectives of the Qur'anic literary text which have a specific meaning relationship with intrinsic elements such as ideas, ideas, and language styles used in the Qur'anic text through translation with several stages of the research process. First, read the text of the Qur'an carefully. Second, translating the literary texts of the Qur'an, which is the source of the study. Third, compare and assess the meaning of the literary text of the Qur'an with the structure of other Qur'anic texts. Fourth, provide interpretations and conclusions from the results of the 'intertext' analysis method on the meaning of the text of the Qur'an from the literary aspect. This study finds that the text of the Qur'an has a close relationship with literary and theological studies in revealing the quality of literary meaning, which is the source of linguistic discourse through a combination of linguistic interpretation and academic ideology. Through various styles of language, the Qur'an is smooth, eloquent, and effectively able to guide and direct religious emotions. In addition, this research can be used as a scientific reference in analyzing the literary texts of the Qur'an.